Level Aktivitas Fisik dan Kualitas Hidup Warga Lanjut Usia - Syamsumin Kurnia Dewi (Media Kesehatan Masyarakat Indonesia, 2018)
A previous study showed active participation in physical exercise program was the major factorrelated to better quality of life in Community Elderly Care Services (CECS) participants. This study,therefore, undertaken to know the relationship between physical activity level and quality of life ofthe elderly at Bambanglipuro subdistrict, Bantul. A cross-sectional study was conducted from June-September 2017. Samples were 123 elderly subjects selected with consecutive sampling technique.Physical activity level was measured with IPAQ-short form. Quality of life was measured with The SF-36 Health Survey, including the Physical Component Summary (PCS) and Mental Component Summary(MCS). Data then were analyzed using chi-square test and Multiple Logistic Regression. Results showedmost of the elderly have better PCS and MCS (69,1%;76,4%). Multivariate analysis showed high physicalactivity level and the absence of hypertension was related to better PCS (aPR=9.38; 95%CI=1.81-48.45 vs aPR=5.12; 95%CI=1.55-16.93) and better MCS (aPR=11.87; 95%CI=2.50-56.33 vs aPR=4.39; 95%CI=1.16-16.70). High physical activity level and the absence of hypertension were related tobetter quality of life of the elderly.